Experts, please help me with the following questions attached below in the image.

Questions are from chapter POLYNOMIALS, grade 9

(please answer all of them, request)

Asked by prakash.sanyasi | 27th Dec, 2019, 03:45: PM

Expert Answer:

(1) 1- 64a3 - 12a + 48a2
 
= (1)3 - (4a)3 - 3(1)2 (4a) + 3(1)(4a)2
= (1 - 4a)  .... since (a - b)3 = a3 - b3 - 3a2b + 3ab2
 
(2) a3 - b3 + 1 + 3ab
 
=(a)3 + (-b)3 + (1)3 - 3a(-b).1
 
[We know that,
 
x3 + y3 + z3 - 3xyz = (x + y + z)(x2 + y2 + z2 -xy - yz - xz)]
= (a - b + 1)(a2 + b2 + 1 + ab + b - a)

Answered by Yasmeen Khan | 27th Dec, 2019, 05:09: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.